Anticorrosive nanosized LiF thin film coating for achieving long-cycling stability of LiCoO2 at high voltages. Issue 7 (1st April 2022) - Wei, Jian; Ji, Yuxuan; Liang, Di; Chen, Bing; Jiang, Chao; Li, Xueting
Abstract: The mutability of layered structures and unfavorable side reactions between cathodes and traditional electrolytes are barriers for the commercialization of LiCoO2 (LCO) at high voltages (above 4.2 V). Metal fluorides, owing to their effective passivation effect, have been considered promising coating materials for various electrochemical applications. As a chemical stability species, LiF can combine the advantages of fluorides with those of lithium without introducing extra elements. In this study, we deposited a uniform nanosized LiF thin film coating onto the LCO particles by coprecipitation to enhance the reversible capacity and cycle stability of the LCO batteries at high voltage. Electrochemical tests indicated that at room temperature, the LCO@LiF cell exhibited an excellent capacity retention with 71.4% after 300 cycles, which is higher than that of many reported oxide and fluoride coatings for LCO at high voltage. This study demonstrated that LiF, an outstanding cathode surface protection layer, can hamper the immediate contact of LCO with the electrolyte, stabilize the LCO surface structure, and successfully protect the cathode from corrosion by the electrolyte. Consequently, a significant enhancement of the electrochemical properties of the LiF-coated LCO was observed. This study provides a facile commercial approach for the mass production of high-voltage LCO cathodes.